2013
DOI: 10.3126/ajms.v4i3.6992
|View full text |Cite
|
Sign up to set email alerts
|

The anti-diabetic activities of the methanol leaf extract of Phyllanthus amarus in some laboratory animals

Abstract: Background:Phyllanthus amarus is used in Nigeria and other parts of the world as a medicinal plant. Aim and objective:The plant is being evaluated for antidiabetic potential because diabetes mellitus has assumed a worldwide dimension and plant with safe potential are being deployed as they are available all year round and are cheap for use by the rural populace. Materials and Methods:The antidiabetic effect of the methanol extract (ME) of Phyllanthus amarus was evaluated in rats. Standard phytochemical methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Some authors have also demonstrated the in vitro and in vivo antioxidant activity of extracts of P. amarus [99,104] . Up to a dose of 1600 mg/kg per os, aqueous leaf extracts did not cause deaths or visible signs of toxicity [105]. The aqueous and hydroethanolic extracts of the whole plant do not show acute toxicities at 5000 mg/kg and subchronic at 3000 mg/kg orally in mice and rats respectively [106].…”
Section: Phyllanthus Amarus Schum and Thomas (Euphorbiaceae)mentioning
confidence: 99%
“…Some authors have also demonstrated the in vitro and in vivo antioxidant activity of extracts of P. amarus [99,104] . Up to a dose of 1600 mg/kg per os, aqueous leaf extracts did not cause deaths or visible signs of toxicity [105]. The aqueous and hydroethanolic extracts of the whole plant do not show acute toxicities at 5000 mg/kg and subchronic at 3000 mg/kg orally in mice and rats respectively [106].…”
Section: Phyllanthus Amarus Schum and Thomas (Euphorbiaceae)mentioning
confidence: 99%
“…Decline in blood glucose and significant recovery in body weight, reduction in the activities of glucose-6-phosphatase and fructose-1-6-disphosphatase in liver, increase in the activity of glucokinase in liver [374] Plant extract Reduction on the glucose level, no visible lesion seen in the liver, kidney and pancreas [375] Plant extract (three pure pentacyclic triterpenoids, oleanolic acid, ursolic acid and lupeol)…”
Section: Phyllanthinmentioning
confidence: 99%
“…An advantage associated with TDD includes avoidance of first past metabolism and variable absorbent including patient compliance. Some of the plants commonly used in the treatment of diabetes mellitus are Gymnema sylvestre, Murraya konige, Ocimum sanctum, Coccinia indica, Phyllanthus amarus [17], etc. S. mahagoni, a plant used in ayurvedic medicine, is useful in treating burning sensation, constipation, leprosy, worm infection bronchitis, inflammations, anemia, and diabetes (Source:www.celastineindia.com/ pankajoudhias).…”
Section: Introductionmentioning
confidence: 99%